Far Field Optical Properties of a Monolayer of SiO2 Spheres and Small Au Nanoparticles. (19th February 2019) - Gómez, A. Santos; González, A. L.
ABSTRACT: Here, we present a numerical study of the far field optical response of a monolayer composed by an hexagonal closed packed array of SiO2 spheres with a single Au NP at each interstitial position. The Optical Efficiencies, Reflection, Transmission and Absorption at normal incidence, were calculated using Discrete Dipole Approximation model extended to periodic targets. In order to consider different amounts of loads of Au NPs per unit of area in the monolayer, we have fixed the diameter of Au NPs (9 nm) and varied the diameter of the SiO2 spheres. The numerical calculations indicate that Au-SiO2 composite monolayers can absorb and scatter the incident electromagnetic wave, as the load of Au NPs increases the monolayer becomes less transparent to light and the spectra are red-shifted. The profile of the absorption spectrum of the Au-SiO2 composite monolayer is very similar to that of a Au NPs monolayer (composite monolayer without the Silica spheres) but less intense, presumably because the Silica spheres screen the coupling of the Localized Surface Plasmons of Au NPs.